Crimal Law Policy Formulation Asset Deprivation of Crimal Action Results - Sri Ismawati; Slamet Rahardjo (Universitas Sriwijaya, 2020)
: In this era the characteristics of crime are marked by the shorter mileage of crime that affects the locus and tempus of crime, changes on sophisticated modus crime that made an accelerates the flow of information and communication of crime and the circulation of money from proceeds of crime that are not tracked through the banking system. The results of Criminal Statistics Publications, the anatomy of crime is clearly visible in Indonesia, although it is still dominated by conventional crime, the data shows that the biggest losses are contributed by new-dimensional crimes, such as narcotics, money laundering, human trafficking and corruption. It is this threat, potential and loss arising from crime that carries the idea of the Formulation of Criminal Law Policy on the Seizure Asset of Criminal Asset Outcome. Theoretical, social and juridical arguments for the phenomenon of proceeds of crime that are difficult to seize in the justice system through criminalization, provide an access to policies to seize assets outside of law criminalization. The important urgency for the future is the formulation of policies on the seizure of assets resulting from crime based on the existence of several considerations, including the massive development of crime that accompanies the growth of industry, business, trade and global finance, the existence of several criminal acts which recorded the most causing losses but difficult to be deprived of the results of the crime, confiscation of assets in the Indonesian legal system can be done after the law enforcement process obtains a court decision that has a permanent power, which requires a long time so that this opportunity can be utilized by the perpetrators of crime to hide or bring assets outside the State so that it is not tracked and Indonesia has ratified the convention The United Nations Against Corruption in 2003 and the eradication of the crime of laundering which outlines the importance of confiscation of assets without conviction. The criminal law policy of appropriation of assets can be carried out by using the concept of a criminal law formulation policy either through criminal justice channels or outside the criminal justice mechanism. Therefore it is important to build a policy framework in the format of substance as the basis for norms of appropriation of assets and the basist of leggal officer in actions, structure as an area of institutional authority in enforcing the appropriation of assets, and upholding human rights